UJI TOKSISITAS, AKTIVITAS ANTIOKSIDAN DAN KADAR METABOLIT SEKUNDER DAUN KEMANGI (Ocimum X africanum lour) - Timotius Timotius; David Limanan; Frans Ferdinal (Jurnal Muara Medika dan Psikologi Klinis, 2021)
High pollutant level has caused an increase in disease that is correlated to Reactive Oxygen Species through a condition that is oxidative stress. Oxidative stress can be stabilized with antioxidants by stabilizing active and unstable radicals to become inactive and stable. Basil leaves (Ocimum x africanum lour) are known to posses antioxidant composition. The aim of this study is to determine the antioxidant ability and toxicity level of basil leaves. The research was conducted through an in vitro experimental study design and bioassays. Extraction of this research was carried out by maceration method using methanol as solvent. The tests were carried out in the form of antioxidant capacity tests using the 1,1-diphenyl-2-picrylhydrazyl method, toxicity tests using the brine shrimph lethality test method on Basil Leaf extract. In basil leaf extract, the antioxidant capacity test obtained IC50 of 174.04 ?g/mL, phenolic level test was 10872,92 mg/mL, alkaloid level test was 8.15 ?g/mL, toxicity test obtained LC50 of 158.36 ?g/mL. This study concludes that basil leaves contain antioxidants not as much as vitamin C however basil leaves do not have an effect that triggers an increase in stomach acid, so it has potential as an alternative antioxidant for a patient with stomach acid disorder, in addition, basil leaves also have cytotoxicity activity that is possible to be used as anti-carsinogen.